Internationalization of Higher Education: Converging or Diverging Trends? - Egron-Polak, Eva (International Higher Education, 2014)
Offering a glimpse at the results of the most recent global survey on internationalization of higher education conducted by the International Association of Universities (IAU), the article focuses on a few findings that show the growing importance of internationalization policies/strategies for higher education institutions worldwide as well as the strong role played by institutional leadership. A discussion of the perceived risks for institutions and for society serves to demonstrate some converging trends while also pointing out the persistent differences and variations between HEIs in different geographic regions of the world. Some analysis of the responses to questions about funding of internationalization is used to highlight the complexity of the picture drawn by the findings of this 4th Global Survey.